Towards a Socio-Cultural Framework of Disability in Morocco - Taswari, Amine; Kandoussi, Mohamed (Advances in Social Sciences Research Journal, 2025)
The Social Model of Disability posits that individuals are disabled by societal barriers, not by their inherent impairments or differences. This conceptual framework emerged as the culmination of ideas and heightened awareness within the disability rights movements during the 1960s and 1970s in Europe and the United States. The widespread adoption of the Social Model and its core principles has significantly influenced policy-making, profoundly impacting the living conditions of individuals with disabilities. Despite its noteworthy contributions, the implementation of the Social Model alone does not comprehensively address the challenge of achieving inclusion. This paper aims to delineate the pitfalls associated with the Social Model of Disability, as elucidated by authorities in the field. It argues for a more effective approach that involves the integration of both the Social Model and the Cultural Model, which values disability as a facet of human diversity. This combination is particularly pertinent in the Moroccan context, where traditionalist models of disability persist. By examining and synthesizing these models, this paper postulates that a comprehensive framework should emerge, better suited to addressing the complexities of disability and fostering inclusion in diverse cultural contexts.